Global Diversity Character Development for Students through Economic Learning - Ninik Indawati (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
Associated with patterns of habituation, teachers can cultivate character through learning ethics, manners, and pronouncing words that are appropriate to the local context. One of the school's strategies can also get students used to saying the word